Analysis Of Women's Leadership Role in Gender Perspective in Work Training Centers (Blk) Batusangkar - Ernawati, Ernawati; Febrian, Vicky Rizki; Fazis, Muhammad; Syam, Herma Yulis (AGENDA: Jurnal Analisis Gender dan Agama, 2022)
It has become a common problem if gender issues are still warm to be discussed. This study aims to determine the impact of a woman's leadership. By lifting the task of a woman's authority, namely Mrs. Rizki Fauzi Oktoria Duha as the Head of the Batusangkar BLK. The research strategy used is a qualitative method of phenomenological approach, namely by tracking the reality of valid execution, describing data whether payments are in accordance with vulnerable factors according to ongoing conditions. The results of the review show that what was done by Ms. Rizky Fauzi Oktoria Duha as the Head of the Batusangkar BLK has properly positioned herself as an influential person in the institution. This was obtained from the results of meetings and perceptions with several respondents who varied in dissecting the orientation of women's administrative work, almost all of the results showed positive results for each of the respondents studied.